Stress Peptic Ulcers in a Sample of Iraqi Patients (Iraqi Journal of Medical Sciences, 2023)
Background: Psychological stress may cause stress peptic ulcers, regardless of Helicopecter pylori (H. pylori) infection or use of non-steroidal anti-inflammatory drugs (NSAID). Studies of sociodemographic characteristics and peptic ulcers identified various risk factors, such as low salary, household member crowding, unemployment, marital strain, and psychological and physical stress.Objective: To determine the clinical picture of stress peptic ulcer in a sample of Iraqi patients. Methods: A cross-sectional study was performed in Al-Imamein Al-Khadimein Medical City, Iraq to determine the clinical features of stress peptic ulcer in a sample of Iraqi patients. Sample collection was done in a period of two years, from April 2021, to April 2023. At first, the process was explained to the patients and informed consent taken from all enrolled individuals. The diagnosis of stress peptic ulcer was done by gastroduodenoscopy, or by laparotomy for acute abdomen (perforated stress ulcer). All selected patients were tested for the presence of active H. pylori infection by stool antigen test (and it was negative). The patients were divided into two groups; Group A patients were presented as an (emergency cases) with complications of stress peptic ulcer either perforation or upper gastrointestinal bleeding stress ulcer; and Group B patients were presented with dyspepsia (as a cold cases), proved by gastroduodenoscopy to be due to stress peptic ulcer.Results: A total of 86 patients with stress ulcer, 37 (43.02%) males, and 49 (56.97%) females, their age ranged from 13-76 years (mean age 36.16±76 years). Group A were 31 (36.04%) patients, their presentations were either acute abdomen proved to be due to perforated stress ulcer by laparotomy in 8 (9.30%) patients, or hematemesis in 23 (26.74%) patients. Group B were 55 (63.59%) patients. The incidence of stress ulcer was 0.02% and the incidence of operations for perforated stress ulcer was 0.01%. The mortality rate was one (1.16%) old female patient with perforated stress ulcer.Conclusion: Stress ulcer can bleed and perforate, so there should be awareness about management of pain, stress and anxiety in all age groups. There should be good and effective postoperative analgesia, reassurance and empathy for patients and advice for protections against stress ulcer when needed.Keywords: Stress ulcer, bleeding, perforationCitation: Atiyah TS. Stress peptic ulcers in a sample of Iraqi patients. Iraqi JMS. 2023; 21(1): 135-144. doi: 10.22578/IJMS.21.1.15
Keywords: Stress ulcer; bleeding; perforation